Dimensions of user experience in enterprise software : Case study of a Finnish HR software vendor - Konkola, Tiina (My University, 2018)
During the last decades Information Technology (IT) has seen reduction in costs and improvements in usability. Due to maturation of technology, interactive products have become more than just usable and useful: the focus has moved to providing outstanding quality experiences. User experience (UX) has become an umbrella term for new, wider ways of understanding the user’s impression of the quality of a product. Emphasis in UX research has been on leisure systems, but the importance of enterprise software UX is growing. Good UX can help enterprise software providers differentiate from competition and increase customer satisfaction. Customer organizations can benefit from good enterprise software UX by improved accuracy, efficiency, and employee satisfaction. However little research has been conducted on enterprise software UX and there is a need to increase knowledge on how UX is constituted particularly in enterprise software. This research contributes to the aforementioned need in the form of a case study with two goals: (1) increasing knowledge on which UX dimensions are considered most important by enterprise software users and (2) providing the case company with knowledge on the current state of UX in their software as well as a suggestion on how to improve it. The case study was carried out utilizing semi-structured interviews and a structured questionnaire, participants being users of the case company’s software i.e. employees in the customer organizations. The results of the study indicate that enterprise software users value pragmatics over hedonics. Pragmatic aspects emphasize task completion while hedonic aspects are related to general human needs such as personal growth and self-expression. The respondents of the questionnaire chose the pragmatic attributes fast to use, easy to use, and reliable as the most important quality attributes of an HR resourcing system. They chose the hedonic attributes creative, fun, and aesthetic as the least important attributes. The interview findings support the suggestion as it seemed that the interviewees were driven mostly by pragmatic goals and the determinants between a positive and a negative user experience seemed to be mostly related to how well they felt the software supported their work task completion. A need to improve the UX of the case company’s software was recognized. It was suggested that the case company starts the process of improving UX from the quality attributes that were considered important by many users, but evaluated poorly. These were: fast to use, reliable, practical, efficient, professional, and supports goal achievement.
Keywords: UX, user experience, enterprise software, käyttäjäkokemus, yritysohjelmistot